(untitled) (Altre Modernità, 2014)
Claire Davison, Béatrice Laurent, Caroline Patey, Natalie Vanfasse (eds.) Provence and the British Imagination (Milano, Ledizioni, 2013, 235 pp. ISBN 978-886-705-137-3) di Paolo Caponi